REPRODUCTIVE PERFORMANCE OF Anodontia philippiana - I Insafitri (Jurnal Kelautan, 2009)
Objective of this study was to determine reproductive performance of A. philippiana. Samples were collected from the oil affected mangrove mudﬂat in Pototan, Guimaras, Philippine on September 2007. A. philippiana were induced to spawn using the serotonin method. Only A. philippiana with shell length of approximately 4.0-5.5 cm were induced to spawn. Three pairs of one ripe female and one ripe male were chosen and placed in aquaria with 3 replicates. A 0.3 ml of 4 rnM serotonin solution (Gros et al., 1997) was injected into 1-2 mm of the gonad of both male and female clams using 0.65 x 25-mm bore hypodermic needle attached to a 5 ml plastic syringe during mid until late afternoon. Number of spawned eggs was calculated, and fertilization was conducted. At 47 h, the percentage of normal (D-larvae) veliger relative to the initial number of eggs was calculated (Massapina et aL, 1999). Larvae from each spawner were reared separately in aquaria for several days without feeding in order to estimate survival rates. The number of larvae we re-estimated every 24-h intervals until total mortality. The decrease in the number of larvae per container we re-calculated as the proportion of live larvae from the initial number of larvae (extinction rate) (Narvarte and Pascual, 2003). Result of this study are total Total spawned eggs (x10 (g m) is 86.11±3.80, Fertilization rate (%) is 83.01±3.13, and harching rate is 36.51+8.64, Length of newly hatched larvae (gm) is 135.73±1.96, Number of days to total mortality (after hatching) without feeding is 9-10 days.Keywords: reproductive, Anodotia philippiana